Importance of Travel Journalism in Uzbekistan: Role and Functions - Adizov Behzod Tursunovich (Genius Journals, 2022)
The article is devoted to an actively developing and very promising direction in journalism - travel journalism (tourism journalism). The article reveals the functions and role of travel journalism.
Keywords: Travel; travel journalism; applied role; journalism